Pyrolysis of Biomass Waste as The Project Based Learning in Community Assistance Course - Imam Sahroni (Universitas Islam Indonesia, 2018)
Community assistance course is a special course for undergraduate student level which need to be finished before doing final thesis project. This course aims to apply the student knowledge which is gained during six semesters in the class. This course is followed by fourty eight students from different department e.g. science, engineering, psychology, law, medicine, and also Islamic studies. We applied a pyrolysis of biomass waste as the tools for Project based learning in community area. We divide fourty eight student into eight teams. Each team was assigned to do some task e.g. literature study, project design, project implementation, and project report based on the pyrolysis project. After the project was finished, we evaluate the grade of each student using the learning outcome which was defined as the goal of the study. Fourty six students acquired grade A, while the other two students acquired grade B. This achievement related to the project based learning that we used in the Community Assistance Course. Keywords: project-based learning, pyrolysis, community assistance course